Analysis of tropospheric ozone climatology in Santa Maria - RS from OMI/MLS instruments - Silva, Karen Leandra Ávila da (2025)
Ozone (O3) is an important trace gas in the atmosphere and one of the main elements of pollution in the tropospheric region. This work aims to analyze the behavior and trends of the tropospheric ozone column (O₃trop) in the city of Santa Maria, Rio Grande do Sul, Brazil (29.42°S and 53.41°W) between 2005 and 2020, using data from the Ozone Monitoring Instrument (OMI) and Microwave Limb Sounder (MLS) instruments on board the AURA satellite, applying the Tropospheric Ozone Residual (TOR) technique. The results revealed a well-defined annual cycle, with minimum values in winter and maximum values in spring, in addition to an increasing trend of 2.3% per decade; high O₃trop concentrations occurred in periods with the action of the La Niña phenomenon. Wavelet analysis highlighted significant interannual influences, associated with phenomena such as the El Niño Southern Oscillation (ENSO) and the Quasi-Biennial Oscillation (QBO).